O desenvolvimento do letramento estatístico por meio de projetos: um estudo com alunos do Ensino Médio - Giordano, Cassio Cristiano (2016)
Statistical literacy is critical for academic education, for professional life, and, above all, for the exercise of empowerment in our society, given the ease of access to data streaming from diverse media. Reading and interpreting these data, as well as expressing ideas informed by them, have become essential for every individual. However, despite the principles conveyed in Brazilian national and state curriculum guidelines, the teaching and learning of statistics have not received their deserved space in São Paulo schools, either in the Caderno do Aluno (a printed material provided by the São Paulo State Department of Education) or in the majority of textbooks marketed for use in high schools. Project-based teaching and learning of statistics constitute opportunities to promote statistical literacy. Moreover, this approach has the potential to change, in a notable manner, the relationship among teacher, student, and knowledge, promoting greater autonomy for students to develop their own research. To analyze the development of literacy and changes in the didactic contract under a project-based approach, a case study was conducted. The subjects were 43 students aged 17-20 years from two classes of the third (i.e., final) year of high school, who were distributed into nine groups of four or five members. During two months they participated in the entire process of developing a statistical investigation, from selecting themes and formulating research questions to the dissemination of results. The results revealed that this approach encourages the development of statistical literacy, creating conditions for a breach of the didactic contract – an important step in the development of students’ autonomy, preparing them for future challenges in their lives, the university, the labor market, and any other situation